CU06-1004-Induced Vascular Normalization Improves Immunotherapy by Modulating Tumor Microenvironment via Cytotoxic T Cells - Park, Songyi; Oh, Ji Hoon; Park, Dong Jin; Zhang, Haiying; Noh, Minyoung; Kim, Yeomyung; Kim, Ye-Seul; Kim, Hyejeong; Kim, Young-Myeong; Ha, Sang-Jun; Kwon, Young-Guen (Frontiers in Immunology, 2021)
Blocking the immune evasion mechanism of tumor cells has become an attractive means for treating cancers. However, the usage of a drug such as nivolumab (αPD-1), which blocks programmed cell death protein 1 (PD-1), turned out to be only effective against certain types of cancer. Especially, vascular abnormal structures of which deter delivery route by leakage and cause the poor perfusion were considered to be environment unfavorable to T cells and immune checkpoint blockade (ICB) delivery within the tumor microenvironment (TME). Herein, we report stabilization of tumor blood vessels by endothelial dysfunctional blocker CU06-1004, which modified the TME and showed synergistic effects with immunotherapy anti-PD-1 antibody. CU06-1004 combination therapy consistently prolonged the survival of tumor-bearing mice by decreasing tumor growth. T-cell infiltration increased in the tumors of the combination group, with cytotoxic CD8+ T cell activity within the tumor parenchyma upregulated compared with anti-PD-1 monotherapy. Tumor inhibition was associated with reduced hypoxia and reduced vessel density in the central region of the tumor. These effects correlated significantly with enhanced expression of IFN gamma and PD-L1 in tumors. Taken together, our findings suggest that CU06-1004 is a potential candidate drug capable of improving therapeutic efficacy of anti-PD-1 through beneficial changes in the TME.